International Comparison of Perceived Ethics Among Business Students - Chen, Alexander N.; Kim, David; Carson, Marsha; Schneider, Simon Paul (Journal of Applied Business and Economics, 2023)
This study extends a pilot study from (Gatlin-Watts, Carson, and Maxwell, 2007) which examined the ethical perceptions of collegiate students from a university in the Southwest United States. Ethical perceptions were measured on ten ethical scenarios, which were grouped into two dimensions: Regulatory and Informational related ethics. The study explores the effect of demographic variables, i.e., age, gender, nationality, and language, on perceptions of ten individual ethical scenarios and two aggregated ethical perceptions among college students. Based on a sample of 922 respondents, age and gender significantly correlated with some of the ethical perception scenarios. Similarly, nationality and language showed a significant relationship with ethical perceptions. Limitations of this study include the limited sample size of international students and the relatively homogeneous sample comprised of mainly business students. Further studies are recommended.